ORGANIZATIONAL AND ECONOMIC PRINCIPLES OF REGULATING MANAGEMENT STYLES BY BUSINESS MANAGERS - Bezzubov, Dmytro; Starodubova, Olga (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Goal: consideration of the issue of organizational principles for ensuring the quality of management, determination of the degree of influence of institutional and organizational tools on the state of the enterprise’s activity from the standpoint of economic prudence and management algorithms and procedures. Research methods: the main scientific methods of system analysis, formal logic and the method of classifications were used. The method of system analysis is applied accordingly to determine the current state of legislation in the field of competences of the head of the enterprise and to regulate the categories of management quality. The method of formal logic made it possible to determine scientific views on the categories of legal elements of the quality of management in the field of management. The method of classifications made it possible to determine the ways of further improvement of institutional methods regarding the influence on the regulation of the enterprise’s activities from the standpoint of management quality. Results: the article examines the problem of enterprise management from the standpoint of the science of administrative and economic law. The problem of management styles of the head of the enterprise as an element of the organization of enterprise activity is presented. The views of scientists on the category of management style as a phenomenon of administrative and economic law are systematized. The management style of the enterprise is presented as a phenomenon of managerial activity and activity to stimulate the personnel of enterprises regardless of the form of ownership. The style of work is not only a personal matter of the manager, as it affects all aspects of the system in one way or another, being a form of realization of economic, socio-psychological and political relations in the process of leading a team. Style is a social phenomenon, because, firstly, it reflects the worldview and beliefs of the leader, and secondly, it largely, often decisively, determines the results of the system. You can cite many examples of how a manager with a progressive leadership style, having led a lagging team, gradually transforms it, awakens creative forces and energy in it, allowing it to eventually become one of the leading ones. The management method is usually interpreted as a set of methods (techniques) of the manager’s purposeful influence on employees and labor teams, which ensure the coordination of their actions. It is important to emphasize that here the method is a completely objective concept that exists outside and independently of the manager, which is determined by the achieved level and the needs of economic development. In contrast, the management style, although fundamentally also objective, is still mediated by the individual properties of the manager. If the objective component of the style is determined by the set of social and economic requirements for managerial activity, its subjective aspects are determined by the personality traits of the manager, primarily by the specifics of his mental makeup. According to the objectively existing circumstances and based on their personal qualities, each manager develops his own style of work. But the differences in style are not limitless, they exist and vary within the limits defined by the leading style concept. A powerful expression of this concept was and remains the management style of work. Nowadays, when measures are being taken to radically improve the management of the economy, the widespread assimilation of the Western style by business personnel, the significance of which is growing over the years, becomes an extreme necessity. Discussion: problems of ensuring management styles are applied from the point of view of the development of economic and civil law.